2012
DOI: 10.1016/j.canlet.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor-targeted photosensitizer selectively inhibits EGFR signaling and induces targeted phototoxicity in ovarian cancer cells

Abstract: Targeted photosensitizer delivery to EGFR expressing cells was achieved in the present study using a high purity, targeted photoimmunoconjugate (PIC). When the PDT agent, benzoporphyin monoacid ring A (BPD) was coupled to an EGFR-targeting antibody (cetuximab), we observed altered cellular localization and selective phototoxicity of EGFR-positive cells, but no phototoxicity of EGFR-negative cells. Cetuximab in the PIC formulation blocked EGF-induced activation of the EGFR and downstream signaling pathways. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 51 publications
5
74
0
Order By: Relevance
“…We observed a trend in reduced number of EOC cells using Cet-BPD(1:7) in the absence of photoactivation (Fig. 5B), which indicates that Cet-BPD possesses similar anti-EGFR and antitumor activity to cetuximab monotherapy (12,36). NIR photoactivation for taPIT (two cycles) achieved a statistically significant mean reduction in tumor burden of 89% relative to untreated mice (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…We observed a trend in reduced number of EOC cells using Cet-BPD(1:7) in the absence of photoactivation (Fig. 5B), which indicates that Cet-BPD possesses similar anti-EGFR and antitumor activity to cetuximab monotherapy (12,36). NIR photoactivation for taPIT (two cycles) achieved a statistically significant mean reduction in tumor burden of 89% relative to untreated mice (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…This quenching phenomenon increases the tumor specificity when optimally designed; however, excess BPD loading results in the loss of cancer cell-specific delivery. In a series of chemical synthesis and in vitro cell culture studies, we previously identified an optimal conjugation ratio of approximately seven BPD molecules per mAb molecule, Cet-BPD(1:7), as a strongly quenched (sevenfold) and cancer cell-specific construct (35) that retains the biological activity of cetuximab (36). These in vitro studies suggest that, like cetuximab, Cet-BPD is trafficked to lysosomes as part of the EGFR internalization and degradation pathway where more than one-half of the Cet-BPD immunoconjugates release BPD resulting in dequenching and activation of both BPD phototoxicity and fluorescence emission in cell culture (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cetuximab) which bind to overexpressed enzymes or receptors in the neoplastic tissue or tumour vasculature [7,141,142]. Photoimmunotherapy using a NIR absorbing phthalocyanine (IR700) conjugated to monoclonal EGFRbinding antibodies triggered in vivo xenograft tumour shrinkage after irradiation with NIR light in EGFR overexpressing cells.…”
Section: Targeted Photosensitizer Deliverymentioning
confidence: 99%
“…Benzoporphyrin derivative monoacid-A conjugated to cetuximab, an anti-EGFR antibody, changes the PS localization within EGFR-positive cells from mitochondria to lysosomes. No phototoxicity was observed in EGFRnegative cells [142]. When the same conjugate was additionally incorporated into Preformed Plain Liposomes to form so called photo-immuno-conjugate-associatingliposomes (PICAL) PDT induced cell killing of ovarian cancer cells was further enhanced [144].…”
Section: Targeted Photosensitizer Deliverymentioning
confidence: 99%